The Effect of Using PORPE Strategy on Improving Iraqi EFL Students’ Reading Comprehension Skills - Dawood, Qassim Hammadi (Journal of College of Education, 2018)
The present study aims at finding out the effect of using PORPE Strategy on improving EFL college students’ reading comprehension skills. To attain the aim of the study, an experiment has been conducted on a sample of (60) EFL students at the Department of English, College of Education, University of Wasit during the academic year 2016-2017. The sample has been distributed into two groups with (30) students in each, a control group taught according to the conventional techniques and an experimental one taught by using the proposed strategy. The two groups have been equalized according to age, levels of parents' education and pre –test scores.          At the end of the experimental instruction period, an achievement test has been administered to both groups. The findings of this test reveal that the results of the experimental group are significantly superior to the results of the control group.          Pedagogical recommendations and suggestions for further research are presented in the light of the results at the end of the study.